Biomedical Advance Studies Involving Cfd Models, Specially In Human Anatomy - Jahid, Md; Parveen, Nikhath; Shekhar Prasad, Chandra (Journal of Neonatal Surgery, 2025)
Biomathematics is the branch of Mathematics where we study those mathematical formulations which are applicable in the field of life sciences. Several biomathematical models have been applying in the field of life sciences for solving complicated and complexioned problems on ecology, growth, viral diseases, cardiovascular diseases etc. Computational Fluid Dynamics (CFD), which is a branch of Mathematics, presently, an important section of Biomathematics, providing Mathematical Models in the studies on human anatomy and human physiology specially related to liquid flow and gaseous flow in human body. In this context, we will discuss about the application of CFD in diagnosis of diseases related to artery (atherosclerosis) circulation of blood through heart valves means heart functioning and further the mathematical design will be studied and investigated in certain circumstances of calculations.